IgA nephropathy after pembrolizumab therapy for mesothelioma. Issue 11 (30th November 2020) - Wang, Ryan; Das, Tathagata; Takou, Anna
Abstract : The use of immune checkpoint inhibitors (CPIs), such as pembrolizumab, for the treatment of cancer, is now prevalent. CPIs are associated with a significant side effect profile, termed immune-related adverse events (irAEs). Renal irAEs, such as interstitial nephritis, are rare, and CPI-related glomerulonephritis even rarer. This is a case report of a 72-year-old man with mesothelioma of the left lung, whose serum creatinine rose during pembrolizumab treatment. Renal biopsy revealed IgA nephropathy. Withdrawal of therapy for 2 months saw no improvement in renal function, and following recommencement, serum creatinine fluctuated at approximately 1.4 times original baseline. This report will highlight the renal irAEs to be the aware of when starting CPIs, and the importance of early renal biopsy in management.